Učinki metode Tomatis na glasbeno učenje šolskih otrok - Zadnik, Katarina (Revija za elementarno izobraževanje, 2019)
The Effects of the Tomatis Method on Music Learning Among School Children. Global research, carried out among adults and children, has shown the positive effects of TM on individuals with special needs. The purpose of this qualitative study, conducted on a sample of three elementary school pupils, attending music school, was to determine the effects of TM on pupils with deficits in the areas of learning in individual and group lessons in music school. The initial state showed problems with attention, concentration, functional musical literacy, and technical skill in playing an instrument. The triangulation of results showed positive improvements in attention, concentration, internal calmness, and body posture while playing the instrument. In the case of one pupil, a significant progress was noted in musical literacy.
Keywords: attention; functional musical literacy; music school; psychomotor domain; Tomatis method